2016
DOI: 10.3171/2015.1.spine14173
|View full text |Cite
|
Sign up to set email alerts
|

Association between intermittent low-back pain and superior cluneal nerve entrapment neuropathy

Abstract: OBJECT Superior cluneal nerve (SCN) entrapment neuropathy (SCNEN) is a cause of low-back pain (LBP) that can be misdiagnosed as a lumbar spine disorder. The clinical features and etiology of LBP remain poorly understood. In this study, 5 patients with intermittent LBP due to SCNEN who had previously received conservative treatment underwent surgery. The findings are reported and the etiology of LBP is discussed to determine whether it is attributable to SCNEN. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 18 publications
0
28
0
3
Order By: Relevance
“…Adelmanesh F [4, 6] reported that trigger points in the superior-lateral quadrant of the gluteal area are highly specific indicators for radicular LBP. Thiese MS [5] found that patients with LBP had pain in the gluteal areas. All of the studies reported an association between radicular LBP and gluteal pain.…”
Section: Discussionmentioning
confidence: 99%
“…Adelmanesh F [4, 6] reported that trigger points in the superior-lateral quadrant of the gluteal area are highly specific indicators for radicular LBP. Thiese MS [5] found that patients with LBP had pain in the gluteal areas. All of the studies reported an association between radicular LBP and gluteal pain.…”
Section: Discussionmentioning
confidence: 99%
“…After the first report of a series of patients whose LBP was ameliorated by SCN decompression at the orifice of the thoracolumbar fascia, 14 others [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] documented LBP due to SCN-E. However, the pathologic background of this type of LBP has not been extensively studied.…”
Section: Discussionmentioning
confidence: 99%
“…The range is from 0 to 24, with higher scores indicating more severe pain. On the NRS, the 6 patients whose LBP had been treated by neurectomy reported LBP alleviation by more than 75% after local nerve block …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations